Photocatalytic Removal of Metronidazole Using Magnetic TiO2 Nanocatalyst (Fe3O4@SiO2@TiO2): Synthesis, Characterization, and Operational Parameters - Ali Esrafili; Saeedeh Khosravi; Mitra Gholami; Mahdi Farzadkia; Ghadir Abdorahimi (Journal of Mazandaran University of Medical Sciences, 2018)
Background and purpose: Photocatalysis process with TiO2 is a well-known method for removal of pollutants from water. However, the small particle size of TiO2, and therefore difficulty in its separation after treatment impede its commercialization. The aim of this study was to synthetize the Fe3O4@SiO2@TiO2 magnetic nanoparticles (NPs) and evaluation of its efficiency in removal of metronidazole (MNZ) from aqueous solutions. Materials and methods: The NPs were synthetized via sol-gel method, and characterized using SEM, XRD, VSM, and BET analysis. Then, the effect of operational parameters, including catalyst dosage, pH, and initial concentration of MNZ on removal efficiency were examined. The order of reaction and kinetic model, as well as the reusability potential of the catalyst were all investigated in the optimum run. Finally, comparison was made between the adsorption, direct photolysis, application of commercial Degussa P25 TiO2 (p25), and Fe3O4@SiO2@TiO2 NPs. Results: The so-synthesized catalyst showed good superparamagnetic properties. The optimum conditions for the MNZ removal were pH=8, the catalyst dosage=1.5 g/L, and initial concentration of MNZ=40 mg/L under 180 min UV irradiation time. The kinetic study revealed that the photocatalytic degradation of MNZ followed the pseudo- first order (R2= 0.9912) and the Langmuir-Hinshelwood model (R2= 0.9976). Conclusion: According to the results, the Fe3O4@SiO2@TiO2 NPs were almost as effective as commercial catalyst Degussa P25 TiO2 in removal of MNZ (P> 0.05). Due to the simple separation with external magnetic field and reusability potential, Fe3O4@SiO2@TiO2 NPs can be considered as a suitable alternative for Degussa P25 TiO2.